Editorial (English) - Mota, Maurício (REVISTA QUAESTIO IURIS, 2016)
DOI: 10.12957/rqi.2016.22590 Editorial for the vol. 09-2 (2016) The Journal Quaestio Iuris, journal classified by MEC / CAPES as Qualis A2, Law, now quarterly, in this volume 09, number 02, is pleased to publish the article Shares And Corporate Financial Debt (Corporate Bonds) In The Classic Rome by Professor Guillermo Suárez Blazquez, professor of Roman Law and Comparative Legal Systems of the University of Vigo, Spain and Editorial Advisor of the Journal Quaestio Iuris. The article Shares And Corporate Financial Debt (Corporate Bonds) In The Classic Rome analyzes in a historical-legal and economic perspective the publicans companies as legal entities creators of stocks, bonds and financial corporate debt in classical Rome. This work was carried out within the framework of DER2013-47662-C2.R Project funded by MINECO (Spanish Government) and ASSIGN. (...)